Block PEO solid polymer electrolyte additive, preparation method and application

By introducing the second block copolymer PSO-PEO-PSO into the PEO molecular segment, the conductivity and mechanical strength problems of solid polymer electrolytes are solved, and the application of lithium-ion battery with high conductivity and wide electrochemical windows is achieved.

CN120349505APending Publication Date: 2025-07-22QINGHAI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510526957.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

The existing solid polymer electrolytes have problems such as low room temperature ion conductivity, low lithium ion migration number, narrow electrochemical window and poor mechanical strength, which limit their application in lithium-ion batteries.

Method used

Using ethylene glycol as the initiator, the phosphazene base catalyst t-BuP4 introduced the second block, and the triblock copolymer PSO-PEO-PSO was synthesized by anionic active polymerization method, and blended with high molecular weight PEO as a macromolecular additive to improve the conductivity and mechanical strength of the electrolyte.

Benefits of technology

The ionic conductivity of the electrolyte is improved to 1.1×10-3S·cm-1, the electrochemical window reaches 5.2V, and the charging and discharge capacity of the first circle reaches 167mAh·g-1, significantly improving the electrochemical performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a block PEO solid polymer electrolyte, a preparation method and application, and relates to the technical field of lithium ion battery materials, ethylene glycol (EG) is adopted as an initiator, a phosphazene base catalyst (t-BuP4) is adopted as a catalyst, a second block is introduced into a PEO molecular chain segment, and a triblock copolymer PSO-PEO-PSO is prepared; the copolymer is doped with a PEO polymer to prepare an electrolyte and is applied to a lithium ion battery. The preparation method has the beneficial effects that the poly-PSO-PEO-PSO triblock copolymer is designed and synthesized through an anionic living polymerization'one-pot method ', and the poly-PSO-PEO-PSO triblock copolymer is used as a macromolecular additive to be blended with high-molecular-weight PEO according to a certain proportion, so that the conductivity of a PEO main body is improved, and meanwhile, the mechanical strength of a polyelectrolyte main chain is improved. Under the condition of 80 DEG C, the ionic conductivity of the blended polyelectrolyte film can reach 1.1 * 10 <-3 > S.cm <-1 >, the blended polyelectrolyte film has an electrochemical window as high as 5.2 V, and the charge-discharge capacity of the first circle is about 167 mAh.g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery materials, and specifically relates to a block PEO solid polymer electrolyte, a preparation method and an application thereof. Background Art

[0002] Due to overcharging or short-circuiting of batteries, many spontaneous explosion accidents have occurred, such as in mobile phones, computers and electric vehicles. At present, more and more scientists are turning to the use of solid electrolytes to replace traditional liquid organic electrolytes.

[0003] As a key component of new energy storage devices, polymer electrolytes have the advantages of easy processing, light weight, low manufacturing cost, high flexibility, etc. Although polymer electrolytes can effectively avoid the battery safety problems caused by liquid electrolyte materials, problems such as low room temperature ionic conductivity, low lithium ion transference number, and narrow electrochemical window that occur in themselves also need to be solved urgently.

[0004] Compared with liquid electrolyte batteries, solid polymer batteries have the advantages that the electrolyte is not easy to leak, the lithium dendrite phenomenon will be reduced, and the battery is safer; although there are also some solid electrolyte products on the market at present, at present, solid polymer electrolytes have not been used on a large scale, which is mainly limited by the defects of PEO itself; due to its low room temperature ionic conductivity (10 -6 -10 -7 S·cm -1 ), its practical application is greatly limited, and it has the disadvantages of narrow electrochemical window and poor mechanical strength at room temperature. The main reason is due to its easy crystallization and high crystallinity. Summary of the Invention

[0005] In order to overcome the disadvantages of the prior art, the present invention prepares a block PEO solid polymer electrolyte, which has high conductivity, a stable electrochemical interface, and a low ionic migration activation energy.

[0006] The present application provides a block PEO solid polymer, using ethylene glycol (EG) as an initiator and phosphazene base catalyst (t-BuP4) as a catalyst, introducing a second block into the PEO molecular chain segment to obtain a triblock copolymer PSO-PEO-PSO, which is the block PEO solid polymer.

[0007] The molecular weight of the block PEO solid polymer is 4-10 kg·mol -1 .

[0008] A preparation method of a block PEO solid polymer includes the following steps: Add purified ethylene glycol (EG) into a reaction flask, add t-BuP4, and cool and distill purified ethylene oxide (EO) into it. React under a closed environment with a nitrogen atmosphere, set the stirring speed at 350 revolutions per minute, control the temperature at 60 °C, react for 24 - 48 h, take a small amount of samples at the preset sampling time for analysis and testing to determine the reaction progress. If the reaction is complete, add styrene oxide (SO), react at 80 °C for 48 - 72 h. When the preset time is reached, take samples for analysis again to observe whether the reaction is complete.

[0009] Before terminating the experiment, take samples for 1H NMR test to determine the polymer structure; meanwhile, take samples for size exclusion chromatography (SEC) test to determine the molecular weight and distribution of the polymer. The finally obtained polymer presents a dark yellow transparent gel. Finally, drop 0.5 ml - 1 ml of acetic acid to terminate the experiment.

[0010] The molar ratio of the ethylene glycol (EG) to t-BuP4 is 1:0.05.

[0011] The molar ratio of the styrene oxide (SO) to the ethylene oxide (EO) is 1:1.50 - 15.00.

[0012] For the purification method of the ethylene glycol, take an appropriate amount of ethylene glycol with a sampling needle in a glove box and inject it into a reaction flask, rinse it, perform azeotropic distillation with THF, open the valve knobs of each gas on the vacuum line to pump out and vacuum the THF in the reaction flask, repeat the rinsing step twice to complete the purification of the drug. Oxygen should not be contacted in this process.

[0013] For the purification method of the ethylene oxide (EO), blow out the air on the vacuum line with a hot air gun, place the reaction flask with pre-added NaH on the vacuum line, introduce an appropriate amount of ethylene oxide under an ice-water bath environment, stir for 6 h under the ice bath, then cool and distill it into the reaction flask with pre-added n-butyllithium, and stir for 30 min under the ice bath to complete the purification of the drug. Oxygen should not be contacted in this process either.

[0014] For the purification method of the styrene oxide (SO), take an appropriate amount of the drug and place it in a flask, add an appropriate amount of CaH2 and stir overnight. The next day, perform vacuum distillation purification in a fume hood, distill it into another flask, and then let it flow into the reaction vacuum bottle after the flow rate is stable.

[0015] A block PEO solid polymer electrolyte uses the described block PEO solid polymer as an additive. The block PEO solid polymer and lithium salt are mixed evenly in a certain proportion, anhydrous acetonitrile is added and heated to dissolve it. After dissolution, it is ultrasonicated for 60 min with an ultrasonic oscillator, then placed in a polytetrafluoroethylene template to process the block PEO solid polymer into a gel state. The block PEO solid polymer gel and a PEO polymer with a molecular weight of 600,000 are used to form a film in a ratio of 6:4.

[0016] A solid polymer lithium battery contains the described block PEO solid polymer electrolyte.

[0017] In this experiment, anionic polymerization technology was used to induce the ring-opening polymerization of ethylene oxide. Specifically, a strong basic catalyst and ethylene glycol were used as initiators. By removing the hydrogen cation on the hydroxyl group of ethylene glycol, an alkoxide substance was formed, which effectively initiated the ring-opening polymerization process of ethylene oxide. The large substituent groups around the phosphorus and nitrogen atoms in the phosphazene base molecule not only provided a good steric hindrance effect for the catalyst but also helped to improve the stability and activity of the catalyst. Phosphazene superbase t -BuP4 has extremely strong Lewis basicity and low nucleophilicity. The general term "Superbases" can completely remove the hydrogen cation from the hydroxyl group of ethylene glycol, making the alkoxide anion fully exposed, having more opportunities to attack the epoxy to open its ring, form a carbon-oxygen bond, and the oxygen anion on the monomer continues to attack the next epoxy to open its ring, and so on, to achieve the ring-opening polymerization reaction (ROP) of ethylene oxide. When the reaction reached the predetermined time, a sample was taken for SEC testing and it was found that the reaction progress had reached the expectation. Then, styrene oxide was added to the reaction flask, and the alkoxide anion then attacked the epoxy on styrene oxide to open its ring, and so on, to achieve the ring-opening polymerization of styrene oxide and finally form a chain segment.

[0018] The present invention uses EG as an initiator and designs and synthesizes poly(styrene oxide- b -ethylene oxide- b -styrene oxide) (PSO-PEO-PSO) triblock copolymer by anionic living polymerization "one-pot method", with controllable molecular weight and clear structure. And the main chain structure of this polymer is the same as that of PEO, both are in the structure of "-C-C-O-", which is different from many existing additives.

[0019] The present invention changes the properties of the polymer by copolymerization. The PSO-PEO-PSO copolymer effectively reduces the crystallinity of PEO, thereby achieving a lower ionic migration activation energy, that is, ions migrate more easily in the electrolyte.

[0020] The block PEO solid polymer is used as a macromolecular additive and blended with high molecular weight PEO in a certain proportion to improve the conductivity of the PEO matrix while enhancing the mechanical strength of the polyelectrolyte backbone. A Li||LiFePO4 button battery is fabricated and its electrochemical performance is tested.

[0021] By analyzing the experimental results, it is found that for the blended polyelectrolyte film at 80 °C, the ionic conductivity can reach 1.1×10 -3 S·cm -1 , and it has an electrochemical window as high as 5.2 V. The high electrochemical window brings a relatively wide voltage range, thus enabling a wider range of electrochemical reactions; allowing the electrode material to withstand higher voltage and current, thereby improving the flexibility and adjustability of reaction regulation.

[0022] In the full cell test, the PSO-PEO-PSO copolymer electrolyte exhibits good battery capacity. At a charge-discharge rate of 0.2 C, it performs strongly, and the initial charge-discharge capacity is approximately 167 mAh·g -1 , and the battery capacity is higher than that of other PEO-based electrolytes and more stable than that of pure PEO-based ones, with a more fitting graph, meeting the discharge standards of the electrolyte.

[0023] The above results indicate that this polymer electrolyte has the potential to be directly used in solid-state lithium-ion batteries, providing a reference for the preparation of PEO-based polyether polyelectrolyte materials. Brief Description of the Drawings

[0024] Figure 1 is a schematic diagram of the operation of a lithium-ion battery; Figure 2 is the molecular formula of PEO (polyethylene oxide); Figure 3 is a schematic diagram of the ring-opening polymerization of ethylene oxide initiated by polyol in the present invention; Figure 4 is the structural diagram of the ring-opening polymerization of ethylene oxide initiated by polyol in the present invention; Figure 5 is the GPC characterization of EGES1 in the present invention (left) and the HNMR spectrum of EGES1 (right); Figure 6 is the SEC characterization of EGES2 (left) and EGES3 (right) initiated by EG in the present invention; Figure 7 is the SEM image of the surface of the block PEO solid polymer electrolyte membrane in the present invention and the elemental distribution map of the lithium salt in the electrolyte (F, N, and S represent fluorine, nitrogen, and sulfur elements in the lithium salt structure respectively); Figure 8 is the DSC curve (left) and TGA curve (right) of EGES1, EGES2, and EGES3 in the present invention; Figure 9 These are the infrared spectra of the EGES3, EGES3-PEO, and EGES3-PEO electrolytes of the present invention; Figure 10 These are the graphs showing the variation of the impedance of EGES1 with temperature from 30°C to 80°C (top), the variation of the impedance of EGES2 with temperature from 30°C to 80°C (middle), and the variation of the impedance of EGES3 with temperature from 30°C to 80°C (bottom) of the present invention; Figure 11 These are the curves showing the variation of the ionic conductivity of the EGES1-PEO electrolyte, EGES2-PEO electrolyte, and EGES3-PEO electrolyte of the present invention with temperature (left); (right) the curves showing the variation of the activation energy of EGES1, EGES2, and EGES3 with temperature; Figure 12 These are the transference numbers of the ions of the EGES3-PEO electrolyte of the present invention (left); the transference numbers of the ions of the pure PEO-based electrolyte (right); Figure 13 These are the electrochemical stabilities of the EGES3-PEO electrolyte of the present invention (top); the electrochemical stability of the pure PEO-based electrolyte (bottom); Figure 14 These are the galvanostatic cycling test curves of the symmetric electrode Li||EGES3-PEO||Li at a current density of 0.1 mA cm −2 at 25°C (left); the galvanostatic cycling test curves of the symmetric electrode Li||PEO||Li at a current density of 0.1 mA cm −2 at 25°C (right); Figure 15 These are the full-cell cycles of the EGES3-PEO electrolyte as a solid electrolyte of the present invention (top); the full-cell cycles of the pure PEO as a solid electrolyte (bottom). Detailed implementation mode

[0025] Example 1: Add 112.0 μL of purified ethylene glycol (EG) to the reaction flask, add 124.0 μL of t-BuP4 (dissolved in n-hexane at 0.8 M), and cold-vaporize 10.0 ml of purified ethylene oxide (EO). React under a nitrogen atmosphere in a closed environment, set the stirring speed to 350 revolutions per minute, control the temperature at 60°C, and react for 24 - 48 h. Take a small amount of samples for analysis and testing at the preset sampling time to determine the reaction progress. If the reaction progresses as scheduled, add 15.20 ml of styrene oxide (SO), react at 80°C for 48 - 72 h. When the predetermined time is reached, take samples for analysis again to observe whether the reaction is complete.

[0026] Before terminating the experiment, samples were taken for 1H NMR testing to determine the polymer structure. Meanwhile, samples were taken for size exclusion chromatography (SEC) testing to determine the molecular weight and distribution of the polymer. The finally obtained polymer presented as a dark yellow transparent gel with a molecular weight of 4 kg·mol -1 , denoted as product EGES1. Finally, 0.5 ml - 1 ml of acetic acid was added dropwise to terminate the experiment.

[0027] For the ethylene glycol described above, its purification method is as follows: In the glove box, an appropriate amount of ethylene glycol was taken with a sampling needle and injected into the reaction flask, rinsed, and distilled azeotropically with THF. Each gas valve knob on the vacuum line was opened to pump out and vacuum-dry the THF in the reaction flask. The rinsing step was repeated twice to complete the purification of the chemical, and oxygen should not be contacted during this process.

[0028] For the ethylene oxide (EO) described above, its purification method is as follows: The air on the vacuum line was blown out with a hot air gun. The reaction flask with NaH added in advance was placed on the vacuum line and an appropriate amount of ethylene oxide was introduced under an ice-water bath environment. After stirring for 6 h under the ice bath, it was cold-vaporized into the reaction flask with n-butyllithium added in advance and stirred for 30 min under the ice bath to complete the purification of the chemical. Oxygen should not be contacted during this process either.

[0029] For the styrene oxide (SO) described above, its purification method is as follows: An appropriate amount of the chemical was placed in a flask, an appropriate amount of CaH2 was added, and it was stirred overnight. The next day, it was purified by vacuum distillation in a fume hood and distilled into another flask. After the flow rate was stable, it was then introduced into the reaction vacuum flask.

[0030] Example 2: 64.0 μL of purified ethylene glycol (EG) was added to the reaction flask, 71.0 μL of t-BuP4 (dissolved in n-hexane at 0.8 M) was added, and 10.0 ml of purified ethylene oxide (EO) was cold-vaporized. The reaction was carried out in a closed environment under a nitrogen atmosphere, with the stirring speed set at 350 revolutions per minute and the temperature controlled at 60 °C for 24 - 48 h. Small samples were taken at preset sampling times for analysis and testing to determine the reaction progress. If the reaction proceeded as scheduled, 5.46 ml of styrene oxide (SO) was added, and the reaction temperature was 80 °C for 48 - 72 h. At the predetermined time, sampling and analysis were carried out again to observe whether the reaction was complete.

[0031] Before terminating the experiment, samples were taken for 1H NMR testing to determine the polymer structure. Meanwhile, samples were taken for size exclusion chromatography (SEC) testing to determine the molecular weight and distribution of the polymer. The finally obtained polymer presented as a dark yellow transparent gel with a molecular weight of 4 kg·mol -1 , denoted as product EGES2. Finally, 0.5 ml - 1 ml of acetic acid was added dropwise to terminate the experiment.

[0032] For the described ethylene glycol, its purification method is as follows: In a glove box, use a sampling needle to take an appropriate amount of ethylene glycol and inject it into a reaction flask, rinse it, perform azeotropic distillation with THF, open the valve knobs on the vacuum line to evacuate the THF in the reaction flask and create a vacuum, repeat the rinsing step twice, and then the purification of the chemical is completed. Oxygen must not be contacted during this process.

[0033] For the described ethylene oxide (EO), its purification method is as follows: Blow out the air on the vacuum line with a hot air gun, place the reaction flask with pre-added NaH on the vacuum line, introduce an appropriate amount of ethylene oxide in an ice-water bath environment, stir for 6 h in the ice bath, then distill it cold into the reaction flask with pre-added n-butyllithium, and stir for 30 min in the ice bath to complete the purification of the chemical. Oxygen must not be contacted during this process either.

[0034] For the described styrene oxide (SO), its purification method is as follows: Take an appropriate amount of the chemical and place it in a flask, add an appropriate amount of CaH2 and stir overnight. The next day, perform vacuum distillation purification in a fume hood, distill it into another flask, and then let it flow into the reaction vacuum flask after the flow rate stabilizes.

[0035] Example 3: Add 48.0 L of purified ethylene glycol (EG) to a reaction flask. μ Add 22.0 L of t-BuP4 (dissolved in n-hexane at 0.8 M), distill cold 10.0 ml of purified ethylene oxide (EO) into it, and carry out the reaction in a closed environment under a nitrogen atmosphere. Set the stirring speed to 350 revolutions per minute, control the temperature at 60 °C, react for 24 - 48 h, take a small amount of samples at the preset sampling times for analysis and testing to determine the reaction progress. If the reaction proceeds as scheduled, add 0.75 ml of styrene oxide (SO), react at 80 °C for 48 - 72 h. When the predetermined time is reached, take samples for analysis again to observe whether the reaction is complete. μ Before terminating the experiment, take samples for 1H NMR testing to determine the polymer structure; at the same time, take samples for size exclusion chromatography (SEC) testing to determine the molecular weight and distribution of the polymer. The finally obtained polymer presents a dark yellow transparent gel-like substance with a molecular weight of 10 kg·mol

[0036] , denoted as product EGES3; finally, drop 0.5 ml - 1 ml of acetic acid to terminate the experiment. -1

[0037] For the described ethylene glycol, its purification method is as follows: In a glove box, use a sampling needle to take an appropriate amount of ethylene glycol and inject it into a reaction flask, rinse it, perform azeotropic distillation with THF, open the valve knobs on the vacuum line to evacuate the THF in the reaction flask and create a vacuum, repeat the rinsing step twice, and then the purification of the chemical is completed. Oxygen must not be contacted during this process.

[0038] For the described ethylene oxide (EO), its purification method is as follows: Blow out the air on the vacuum line with a hot air gun. Place the reaction flask with pre-added NaH on the vacuum line and introduce an appropriate amount of ethylene oxide in an ice bath environment. After stirring for 6 hours in the ice bath, distill it cold into the reaction flask with pre-added n-butyllithium, and stir for 30 minutes in the ice bath to complete the purification of the drug. Oxygen should not be contacted in this process either.

[0039] For the described styrene oxide (SO), its purification method is as follows: Take an appropriate amount of the drug and place it in a flask, add an appropriate amount of CaH2 and stir overnight. The next day, carry out purification by vacuum distillation in a fume hood, distill it into another flask, and then let it flow into the reaction vacuum flask after the flow rate is stable.

[0040] Preparation of block PEO solid polymer electrolyte: Weigh out 5 g of block PEO solid polymer, calculate the amount of lithium salt according to the sum of the molar amounts of EO and SO (1 / 20), mix well, add anhydrous acetonitrile and heat to dissolve it. After dissolution, ultrasonicate it with an ultrasonic oscillator for 60 minutes, then put it into a polytetrafluoroethylene template, wrap it with tin foil (puncture the tin foil with many small holes) to facilitate the volatilization of anhydrous acetonitrile, place it in a fume hood and blow for 12 hours, and then put it into a vacuum drying oven, heat it at 60 °C and dry for another 12 hours to bake out all the anhydrous acetonitrile. The block PEO solid polymer becomes a gel state. Spread the block PEO solid polymer and the PEO polymer with a molecular weight of 600,000 in a ratio of 6:4 to form a film; obtain EGES1-PEO electrolyte, EGES2-PEO electrolyte, and EGES3-PEO electrolyte.

[0041] Preparation of PEO polymer electrolyte (control group): Incorporate pure polyethylene oxide (PEO) with a molecular weight of 600,000 into the lithium salt with the same mass ratio, and make a solid electrolyte through the same preparation method, which is a pure PEO-based electrolyte.

[0042] Preparation of the positive electrode plate: Mix LFP active particles (accounting for 80%), PVDF binder (accounting for 10%), and conductive agent (accounting for 10%) in proportion, and add an appropriate amount of NMP solvent (N-methylpyrrolidone). After several hours of strong stirring, form a well-fluidized and uniform slurry. Subsequently, use a customized scraper to evenly coat the slurry on the carbon-coated aluminum foil. Place the coated aluminum foil in a vacuum drying oven, first dry it at 60 °C for 6 hours, and then raise the temperature to 80 °C and dry for another 12 hours to ensure that the NMP solvent completely volatilizes. After drying, use a punching machine to cut the aluminum foil into circular electrode plates. Finally, compact the electrode plates with a press to remove the surface burrs and obtain the LFP positive electrode plate.

[0043] Assembly of button batteries: In a glove box under an argon atmosphere, symmetric cells, full cells, blocking cells, and LSV cells were assembled using CR2025 button cell casings. Before testing, the above-mentioned various types of solid-state button cells were placed in a high and low temperature chamber at 70 °C for 8 hours to improve the interfacial physical contact between the electrodes and the PEO-based electrolyte.

[0044] Spectrum characterization and test analysis: The block PEO solid polymer was characterized by size exclusion chromatography (SEC) and nuclear magnetic resonance hydrogen spectroscopy ( 1 HNMR). According to the NMR spectrum and SEC curve, it was shown that after adding SO, the molecular weight of the polymer increased significantly, and NMR could prove that the part where the molecular weight increased was the second block.

[0045] DSC tests and thermogravimetric analysis (TGA) were carried out on the block PEO solid polymers EGES1, EGES2, and EGES3, indicating that compared with PEO, the block PEO solid polymers had a lower crystallinity and good thermal stability.

[0046] The surface of the block PEO solid polymer electrolyte was tested by scanning electron microscopy (SEM), and the electron micrograph showed that the surface of the electrolyte membrane was flat and there was no ionic agglomeration.

[0047] Energy dispersive X-ray spectroscopy (EDS) showed that elements such as F, S, and N in the lithium salt were distributed quite evenly in the electrolyte.

[0048] Fourier transform infrared spectroscopy was used to test the block PEO solid polymer, the block PEO solid polymer doped with 600,000 molecular weight PEO at a ratio of 6:4, and the block PEO solid polymer product doped with 600,000 molecular weight PEO electrolyte at a ratio of 6:4. The obtained spectra showed that the lithium salt and the copolymer were well mixed in the block PEO solid polymer electrolyte doped with 600,000 molecular weight PEO at a ratio of 6:4.

[0049] The impedance-temperature variation diagrams of the block PEO solid polymers EGES1, EGES2, and EGES3, the ionic conductivity-temperature variation curves of the EGES1-PEO electrolyte, EGES2-PEO electrolyte, and EGES3-PEO electrolyte, and the activation energy-temperature variation curves of the copolymers EGES1, EGES2, and EGES3 showed that: due to the lower activation energy of the EGES3-PEO electrolyte, it exhibited a higher ionic conductivity, and at a high temperature of 80 °C, this performance was significantly improved, and the ionic conductivity could reach 1.1×10 -3 S·cm -1 , showing excellent ionic transport ability of this electrolyte material.

[0050] According to the ion transference number curves of the EGES3-PEO electrolyte and the pure PEO-based electrolyte, it can be calculated that the lithium ion transference number of the EGES3-PEO electrolyte is 0.35; the lithium ion transference number of the pure PEO electrolyte is 0.22, and this value is similar to that of other PEO-based polymer electrolytes.

[0051] From the comparison of the electrochemical stability curves of the EGES3-PEO electrolyte and the pure PEO-based electrolyte, it can be seen that the electrochemical window of the EGES3-PEO electrolyte is significantly wider than that of the pure PEO-based electrolyte.

[0052] From the comparison of the constant current cycling test curves, (1) the potential of the EGES3-PEO electrolyte is lower than that of the pure PEO-based electrolyte, indicating that the interfacial effect of the EGES3-PEO electrolyte is better than that of the pure PEO-based electrolyte; (2) it shows that the rigidity of the EGES3-PEO electrolyte is better than that of the pure PEO-based electrolyte, and the EGES3-PEO electrolyte can block the penetration of lithium dendrites to a certain extent.

[0053] According to the full cell cycling diagrams of the EGES3-PEO electrolyte and the pure PEO-based electrolyte, it can be seen that at 70 °C, for LFP||EGES3-PEO||Li, at a discharge rate of 0.2C, the battery shows a typical charge-discharge plateau of lithium iron phosphate (LFP), approximately around 3.5V. The initial discharge capacity reaches 167 mAh·g -1 . Similarly, a full cell of LFP||PEO||Li was assembled using the same positive and negative electrode materials, and charge-discharge cycling was carried out under the same conditions. Its initial cycle discharge capacity is 153 mAh·g -1 , which is lower than the battery capacity of our copolymer electrolyte-doped battery. And the potential difference of the charge-discharge voltage plateau of LFP||PEO||Li is significantly higher than that of LFP||EGES3-PEO||Li, indicating that the doped copolymer significantly reduces the crystallinity of PEO, and Li + is more likely to pass through the two-phase interface of LFP||EGES3-PEO||Li.

Claims

1. A block PEO solid polymer, characterized in that, Using ethylene glycol as an initiator and phosphazene base catalyst as a catalyst, a second block is introduced into the PEO molecular chain segment to obtain a triblock copolymer PSO-PEO-PSO, which is a block PEO solid polymer.

2. The block PEO solid polymer according to claim 1, wherein The molecular weight of the block PEO solid polymer described is 4 - 10 kg·mol -1 .

3. A preparation method of a block PEO solid polymer, characterized in that, It includes the following steps: Add purified ethylene glycol into a reaction flask, add t-BuP4, and cold distill purified ethylene oxide. React under a closed nitrogen atmosphere, set the stirring speed to 350 revolutions per minute, control the temperature at 60 °C, react for 24 - 48 h, take a small amount of samples at preset sampling times for analysis and testing to determine the reaction progress. If the reaction is complete, add styrene oxide, react at 80 °C for 48 - 72 h. When the predetermined time is reached, take samples for analysis again to observe whether the reaction is complete; Before terminating the experiment, take samples for 1H NMR testing to determine the polymer structure; at the same time, take samples for size exclusion chromatography testing to determine the molecular weight and distribution of the polymer; the finally obtained polymer presents a dark yellow transparent gel; finally, drop 0.5 ml - 1 ml of acetic acid to terminate the experiment.

4. The preparation method of a block PEO solid polymer according to claim 3, characterized in that The molar ratio of the ethylene glycol to t-BuP4 is 1:0.

05.

5. The preparation method of a block PEO solid polymer according to claim 4, characterized in that, The molar ratio of the styrene oxide to the ethylene oxide is 1:1.50 - 15.

00.

6. The preparation method of a block PEO solid polymer according to claim 5, wherein, For the ethylene glycol, its purification method is: use a sampling needle to take an appropriate amount of ethylene glycol in a glove box and inject it into the reaction flask, rinse, perform azeotropic distillation with THF, open the valve knobs of each gas on the vacuum line to pump out and vacuum the THF in the reaction flask, repeat the rinsing step twice to complete the purification of the drug, and oxygen should not be contacted in this process.

7. The preparation method of a block PEO solid polymer according to claim 6, characterized in that, For the ethylene oxide, its purification method is: blow out the air on the vacuum line with a hot air gun, place the reaction flask with pre-added NaH on the vacuum line and introduce an appropriate amount of ethylene oxide in an ice bath environment, stir for 6 h under ice bath, then cold distill it into the reaction flask with pre-added n-butyllithium, and stir for 30 min under ice bath to complete the purification of the drug. Oxygen should not be contacted in this process either.

8. The preparation method of a block PEO solid polymer according to claim 7, characterized in that, For the styrene oxide, its purification method is: place an appropriate amount of the drug in a flask, add an appropriate amount of CaH2 and stir overnight, and perform vacuum distillation purification in a fume hood the next day, distill it into another flask, and then flow it into the reaction vacuum flask after the flow rate is stable.

9. A block PEO solid polymer electrolyte, which uses the block PEO solid polymer described in claim 1 or the block PEO solid polymer prepared according to any one of claims 2-7 as an additive, is characterized in that, Mix the block PEO solid polymer and lithium salt in a certain proportion, add anhydrous acetonitrile and heat to dissolve it. After dissolution, ultrasonically vibrate it with an ultrasonic oscillator for 60 min, then put it into a polytetrafluoroethylene template to process the block PEO solid polymer into a gel state, and spread the block PEO solid polymer gel and a PEO polymer with a molecular weight of 600,000 in a ratio of 6:

4.

10. A solid polymer lithium battery, characterized in that, It includes the block PEO solid polymer electrolyte described in claim 8.